ANALISIS KESULITAN GURU DALAM IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DI KELAS V UPTD SD NEGERI KENARILANG - Yahfet K Hamap; Jon A Lalang Yame; Triznawasti Y Daik (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2026)
The research problem is "teacher difficulties in implementing the independent learning curriculum in grade V of the Kenarilang State Elementary School Technical Implementation Unit (UPTD SD Negeri Kenarilang). This type of research uses qualitative research conducted at the UPTD SD Negeri Kenarilang. This study aims to analyze the difficulties faced by teachers in implementing the independent learning curriculum in grade V of the UPTD SD Negeri Kenarilang. The difficulties faced by the Grade V teachers of the UPTD SD Negeri Kenarilang include planning the difficulties of teachers in implementing the independent learning curriculum in grade V of the UPTD SD Negeri Kenarilang, implementing the difficulties of teachers in implementing the independent learning curriculum in grade V of the UPTD SD Negeri Kenarilang, and assessing the difficulties of teachers in implementing the independent learning curriculum in grade V of the UPTD SD Negeri Kenarilang. The data sources in this study are primary data, secondary data, and information from the principal and grade V teachers of the UPTD SD Negeri Kenarilang. The qualitative data analysis technique uses condensation. Data analysis, data presentation, and conclusion drawing. The results of the study indicate that the principal and fifth-grade teachers at the Kenarilang Elementary School UPTD have implemented learning and assessment planning, student-centered learning, integrated assessment and learning, and implemented learning objective planning.